2017
DOI: 10.1186/s10194-017-0807-1
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CGRP in migraine patients – a review of pros and cons

Abstract: Migraine is the most prevalent neurological disorder worldwide and it has immense socioeconomic impact. Currently, preventative treatment options for migraine include drugs developed for diseases other than migraine such as hypertension, depression and epilepsy. During the last decade, however, blocking calcitonin gene-related peptide (CGRP) has emerged as a possible mechanism for prevention of migraine attacks. CGRP has been shown to be released during migraine attacks and it may play a causative role in indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
178
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(182 citation statements)
references
References 83 publications
2
178
0
2
Order By: Relevance
“…Calcitonin gene‐related peptide (CGRP) is a promising target to treat migraine, which has a crucial role in migraine pathophysiology. And CGRP antagonisms and CGRP monoclonal antibody (mAb) are the drugs to inhibit the CGRP pathway resulting in the migraine treatment (Deen et al, ; Deneris, Rosati Allen, Hart Hayes, & Latendresse, ; Messlinger, ; Negro, Lionetto, Simmaco, & Martelletti, ; Schuster & Rapoport, ; Yuan, Lauritsen, & Kaiser, ). Some of CGRP antagonisms related clinical trials are discontinued because of the liver injury after repeated administrations (Hong & Liu, ; Hong, Wu, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Calcitonin gene‐related peptide (CGRP) is a promising target to treat migraine, which has a crucial role in migraine pathophysiology. And CGRP antagonisms and CGRP monoclonal antibody (mAb) are the drugs to inhibit the CGRP pathway resulting in the migraine treatment (Deen et al, ; Deneris, Rosati Allen, Hart Hayes, & Latendresse, ; Messlinger, ; Negro, Lionetto, Simmaco, & Martelletti, ; Schuster & Rapoport, ; Yuan, Lauritsen, & Kaiser, ). Some of CGRP antagonisms related clinical trials are discontinued because of the liver injury after repeated administrations (Hong & Liu, ; Hong, Wu, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration is CGRP expression in the anterior pituitary. The pituitary gland is outside the blood‐brain barrier, and anti‐CGRP mAbs could theoretically affect pituitary function, such as by reducing growth hormone secretion …”
Section: Cgrp Physiology and Corresponding Clinical Recommendations Rmentioning
confidence: 99%
“…In adults, monoclonal antibodies (mAbs) to calcitonin gene‐related peptide (CGRP), or its receptor, have been shown to be efficacious for migraine prevention, and in episodic cluster headache . Although CGRP is expressed in multiple body systems, trials to date have demonstrated minimal adverse events. The most commonly seen adverse events in adult trials included: injection site reactions, upper respiratory symptoms, and constipation.…”
Section: Introductionmentioning
confidence: 99%
“…Erenumab had only a small effect on angina during treadmill exercise in patients with coronary artery disease (however, see Maassen van den Brink et al). Drug‐drug interactions are very unlikely with mAbs . Nonetheless, identifying subtle effects that may become consequential under particular circumstances or with long‐term use will require more experience with the drugs .…”
mentioning
confidence: 99%